2009
DOI: 10.1016/j.dsr2.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oil-based drill mud disposal on benthic foraminiferal assemblages on the continental margin off Angola

Abstract: In order to assess the possible environmental impact of oily cuttings discharged during oil exploration activities, we studied the benthic foraminiferal faunas in a five-station, 4-km-long sampling transect around a cuttings disposal site at about 670 m depth offshore Angola (W Africa), where drilling activities started 1.5 years before sampling. Living (Rose Bengal stained) and dead foraminiferal faunas were sampled in March 2006. The faunal patterns mirror the spatial distribution of hydrocarbons, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 84 publications
(112 reference statements)
1
34
1
3
Order By: Relevance
“…Previous studies showed that foraminiferal communities rapidly change under organic pollution exposures associated with fish farming (Scott et al 1995, Angel et al 2000, Vidovi et al 2009. Foraminifera are also good indicators of the impact of offshore drilling activities (Mojtahid et al 2008, Jorissen et al 2009, Denoyelle et al 2010, Schwing et al 2015 and heavy metal pollution (Bergin et al 2006, Frontalini et al 2009). However, all of these studies were restricted to the hard-shelled species microscopically identified in dried sediment samples (Schön -feld et al 2012, Alve et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that foraminiferal communities rapidly change under organic pollution exposures associated with fish farming (Scott et al 1995, Angel et al 2000, Vidovi et al 2009. Foraminifera are also good indicators of the impact of offshore drilling activities (Mojtahid et al 2008, Jorissen et al 2009, Denoyelle et al 2010, Schwing et al 2015 and heavy metal pollution (Bergin et al 2006, Frontalini et al 2009). However, all of these studies were restricted to the hard-shelled species microscopically identified in dried sediment samples (Schön -feld et al 2012, Alve et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The BIOZAIRE program, for example, was initiated in 2000 to characterize the benthic community of the continental margin in the Gulf of Guinea, specifically the Congo River submarine channel and deep-sea fan (Jorissen et al 2009). The BIOZAIRE surveys, conducted from 2000 to 2005, involved sediment sampling and mooring deployments at 11 different sites in various habitats ranging from 350-4800 m water depth, including hydrocarbon seeps and coral outcrops.…”
mentioning
confidence: 99%
“…Due to some peculiar features, like the short life cycles and the high turnover rate, together with the good preservation of the tests, the high abundance in marine sediments, the worldwide distribution and the high number of specimens that can be retrieved from a relatively small sample (a few cm 3 of sediment), foraminifera have a potential higher than macrofauna to reveal changes in environmental conditions (Alve 1995;Debenay et al 1996;Scott et al 2005;Murray 2006;Alve et al 2009;Cherchi et al 2009;Jorissen et al 2009;Frontalini and Coccioni 2011;Bouchet et al 2012;Schönfeld et al 2012;Barras et al 2014;Martins et al 2015a, c). Generally, their response to natural stress and/or anthropogenic impact can be observed at both the community (total abundance, species richness and ecological diversity) and the species levels (e.g.…”
Section: Benthic Foraminiferamentioning
confidence: 95%